Association between levels of physical activity and low handgrip strength: Korea National Health and Nutrition Examination Survey 2014-2019 - Hyungsoon Ahn; Hwa Young Choi; Moran Ki (Epidemiology and Health, 2022)
OBJECTIVES This study aimed to investigate the association between levels of physical activity (PA) and low handgrip strength in Korean adults. METHODS Our cross-sectional study design included 24,109 Korean adults older than 19 years of age who participated in the Korea National Health and Nutrition Examination Survey 2014–2019. Low handgrip strength is described as hand strength less than the cut-off value of the 20th percentile of handgrip strength from a healthy population in each gender and age group. PA was categorized into three levels (inactive, active, and highly active) according to the World Health Organization’s global recommendations on PA for health. Multivariable logistic regression analysis was used to examine the association between levels of PA and low handgrip strength. RESULTS Odds ratios (ORs) for low handgrip strength were significantly higher in middle-aged women who were active (adjusted odds ratio [aOR], 1.40; 95% confidence interval [CI], 1.15 to 1.69) and inactive (aOR, 1.47; 95% CI, 1.23 to 1.76) than in those highly active in walking exercise. Most of older people had significantly higher ORs for low handgrip strength in active compared to highly active in the context of aerobic, muscle strengthening, and walking exercise. CONCLUSIONS Walking exercise was associated with a lower risk of sarcopenia in middle-aged women and older individuals. However, further studies are necessary to confirm the causal relationship between levels of PA and low handgrip strength.